Knowledge, Attitudes, and Practices among Dental Practitioners Regarding Antibiotic Prescriptions for Pregnant and Breastfeeding Women in the Dominican Republic - Javier Aragoneses; Ana Suárez; Cinthia Rodríguez; Juan Algar; Juan Manuel Aragoneses (MDPI AG, 2021)
In this study, we aimed to explore the trends among dentists in the Dominican Republic of providing antibiotic prescriptions to pregnant/breastfeeding dental patients. A survey was conducted among 98 dentists, using a self-administered questionnaire, about their knowledge and attitudes regarding antibiotic usage in pregnant/lactating women and the translation of these into practice. The majority of the survey population were female dentists (63.3%) aged 45-54 years. A chi-square test showed statistically significant differences in the knowledge sources between older and younger dentists, with a minority having chosen scientific literature as a source (p-value of 0.04). There were statistically significant associations between gender and certain attitudes and practice-based questions, with p-values of 0.04 and 0.01, respectively. The Spearman's correlation test showed a statistically significant correlation between knowledge and attitude (p-value 0.001), whereas no correlation was found with practice (p-value 0.23). A multiple response analysis showed that the majority of the respondents chose the second and third trimester for antibiotic prescriptions for acute conditions such as cellulitis, periodontal abscess, and pericoronitis. Most dentists had sufficient knowledge about antibiotic usage in pregnant/lactating women, but it did not translate into practice, and a certain proportion of the participants followed incongruent drug prescription. These findings can be used to focus on judicious antibiotic usage by dentists in the Dominican Republic.